2022
DOI: 10.21511/imfi.19(3).2022.19
|View full text |Cite
|
Sign up to set email alerts
|

An overview of investor sentiment: Identifying themes, trends, and future direction through bibliometric analysis

Abstract: Investor sentiment is the result of trading behavior and irrational beliefs of investors leading to high volatility and market mispricing. This review aims to study the entire spectrum of articles in the domain of investor sentiment using a bibliometric analysis approach. To this end, the study analyzes a total of 1,919 articles published in the Scopus database between 1979 and 2022. The review uncovers major themes, leading authors, influencing articles, trend topics, top contributing countries, and affiliati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Additionally, by considering other bibliometric studies focusing on sentiment analysis in various areas, the remarkable contributions of both the USA and China have been observed, which in general, held the first positions. The reader can refer to the works of Kamath et al [51] in the area of investor sentiment, Kale [52] in the bibliometric analysis conducted on sentiment analysis in library and information science, and Yaqub et al [53] in the tourism industry, who highlight the top position occupied by the USA and the second position held by China, or to the works of Qiang et al [54] in the area of network public opinion and Nyakurukwa and Seetharam [55] regarding the evolution of social media sentiment in the stock market-who highlight the leader position of China, followed by the USA.…”
Section: Authorsmentioning
confidence: 99%
“…Additionally, by considering other bibliometric studies focusing on sentiment analysis in various areas, the remarkable contributions of both the USA and China have been observed, which in general, held the first positions. The reader can refer to the works of Kamath et al [51] in the area of investor sentiment, Kale [52] in the bibliometric analysis conducted on sentiment analysis in library and information science, and Yaqub et al [53] in the tourism industry, who highlight the top position occupied by the USA and the second position held by China, or to the works of Qiang et al [54] in the area of network public opinion and Nyakurukwa and Seetharam [55] regarding the evolution of social media sentiment in the stock market-who highlight the leader position of China, followed by the USA.…”
Section: Authorsmentioning
confidence: 99%
“…By analyzing other bibliometric papers, it has been observed that the abovementioned countries are also listed among the top contributors for the social media research in the age of COVID-19 [112], COVID-19 vaccination misinformation [40], health-related misinformation in social media [39], and sentiment analysis in times of COVID-19 [115]. Furthermore, it has been observed that both the USA and China have assumed top positions (either first or second position) regarding the contribution to the various fields such as investors sentiments [119], network public opinion [120], sentiment analysis in library and information science [121], social media sentiment in the stock market [122], and the tourism industry [123].…”
Section: Discussionmentioning
confidence: 99%
“…Academic background in this field is mixed. It is proved by bibliometric research on the stock market indices by Kamath et al (2022) and Zulfikar (2022).…”
Section: Literature Reviewmentioning
confidence: 94%